(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Increasing knowledge in all aspects of life enhance the potential of life span as well qualties which is the cornerstone of survival.In this research we foucose on the diffrent incidence between Libyan cities regarding the summer season Covid-19 pandamic. The results of our study showes a statiscal significance in the number of Covid -19 cases. the study showes a link were cities like first place Tripoli,secand place misurata and in the third place sebha as the major affected cities, followed by other 26 cities ,the main incidenc were in the western part of Libya in relatioins to the population density . The recomodations of the stud to implement W.H.O guide lines and advices by providing protections of the medical and paramedical staff protections suplly of the hospitals with the neceities incresing screening programe and last but not the less awernce between the population is the key factor to breach the spreading chain.